Improving the flame retardancy of polypropylene by nano metal–organic frameworks and bioethanol coproduct. (15th March 2019) - Xie, Jiong; Shi, Xiaowei; Zhang, Mi; Dai, Xiu; Wang, Xinlong
Summary: In this work, a novel flame retardant system based on nano zeolitic imidazolate framework‐8 (ZIF‐8) and the distiller's dried grains with solubles (DDGS) without traditional flame retardants has been designed and blended with polypropylene (PP) to prepare the green flame retarded composites. The influences of nano ZIF‐8 and DDGS on mechanical properties and flame retardancy of PP are studied. The results indicate that combination of nano ZIF‐8 and DDGS improves the mechanical properties of PP, and the tensile strength of the composites containing 29 wt% of DDGS and 1 wt% of nano ZIF‐8 reaches 34.0 MPa compared with 24.7 MPa of pure PP. The limiting oxygen index (LOI) of the composites containing 27 wt% DDGS and 3 wt% of nano ZIF‐8 is about 25.0% compared with 17.5% of pure PP. Besides, its horizontal burning velocity also decreases significantly. The char residues after burning of the PP composites are analyzed, and the mechanism is discussed in detail.